Chemical Composition, Oxidative Stability and Antioxidant Capacity of Oil Extracted from Roasted Seeds of Sacha-Inchi (Plukenetia volubilis L.) - Cisneros, FH (2014)
We thank the financial support from CONCYTEC, Peru (Contract 142-2006-OAJ).